2009
DOI: 10.1532/hsf98.20091066
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Left Ventricular Aneurysms: A Comparison of Long-term Follow-up of Left Ventricular Function for Classic Aneurysmectomy and Endoaneurysmorrhaphy Techniques

Abstract: LV aneurysm can be repaired with acceptable surgical risk. Surgical treatment of LV aneurysm is associated with an improvement in long-term survival and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Lundbald et al [2004] reported that advanced age, 3-vessel disease, and linear repair technique were associated with increased mortality in patients who underwent left ventricular aneurysm repair. However, several studies reported no important significant differences between the 2 techniques in terms of outcomes [Antunes 2005, Erbasan 2009, Mukaddirov 2008, Tavakoli 2002.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lundbald et al [2004] reported that advanced age, 3-vessel disease, and linear repair technique were associated with increased mortality in patients who underwent left ventricular aneurysm repair. However, several studies reported no important significant differences between the 2 techniques in terms of outcomes [Antunes 2005, Erbasan 2009, Mukaddirov 2008, Tavakoli 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports on endovascular circular patch plasty (Dor procedure) for left ventricular aneurysm repair were promising [Sartipy 2005, Dor 1989], which was followed by several studies comparing this technique or modifications with the linear repair technique, with inconsistent results reporting improved outcomes with the Dor procedure or satisfactory outcomes with both procedures [Chen 2010, Erbasan 2009, Chen 2009, Mukaddirov 2008, Parolari 2007, Baev 2006, Antunes 2005, Lundblad 2004, Benetis 2004, Tavakoli 2002. For example, in line with our findings, Dor et al [2004] reported an increase in ejection fraction during follow-up of patients who received endoventricular repair.…”
Section: Discussionmentioning
confidence: 99%
“…выживаемость на фоне медикаментозной терапии варьирует от 47% до 70% [8], при наличии симптомов СН -46% [9]. После хирургической коррекции ПАЛЖ показатель пятилетней выживаемости увеличивается до 90%, а десятилетней -составляет 80% [10]. Основной причиной смерти у пациентов с ПАЛЖ являются желудочковые нарушения ритма, разрыв сердца, СН, повторный ИМ, тромбоэмболические осложнения [7,9].…”
Section: передовая статья обзоры литературыunclassified